SAF-189s, a potent new-generation ROS1 inhibitor, is active against crizotinib-resistant ROS1 mutant-driven tumors - Xia Zong-jun; Ji Yin-chun; Sun De-qiao; Peng Xia; Gao Ying-lei; Fang Yan-fen; Zhao Xing-dong; Wang Wei-bo; Ding Jian; Geng Mei-yu; Ai Jing (Acta Pharmacologica Sinica, 2021)
The ROS1 fusion kinase is an attractive antitumor target. Though with significant clinical efficacy, the well-known first-generation ROS1 inhibitor (ROS1i) crizotinib inevitably developed acquired resistance due to secondary point mutations in the ROS1 kinase. Novel ROS1is effective against mutations conferring secondary crizotinib resistance, especially G2032R, are urgently needed. In the present study, we evaluated the antitumor efficacy of SAF-189s, the new-generation ROS1/ALK inhibitor, against ROS1 fusion wildtype and crizotinib-resistant mutants. We showed that SAF-189s potently inhibited ROS1 kinase and its known acquired clinically resistant mutants, including the highly resistant G2032R mutant. SAF-189s displayed subnanomolar to nanomolar IC50 values against ROS1 wild-type and mutant kinase activity and a selectivity vs. other 288 protein kinases tested. SAF-189s blocked cellular ROS1 signaling, and in turn potently inhibited the cell proliferation in HCC78 cells and BaF3 cells expressing ROS1 fusion wild-type and resistance mutants. In nude mice bearing BaF3/CD74–ROS1 or BaF3/CD74–ROS1G2032R xenografts, oral administration of SAF- 189s dose dependently suppressed the growth of both ROS1 wild-type- and G2032R mutant-driven tumors. In a patient-derived xenograft model of SDC4–ROS1 fusion NSCLC, oral administration of SAF-189s (20 mg/kg every day) induced tumor regression and exhibited notable prolonged and durable efficacy. In addition, SAF-189s was more potent than crizotinib and comparable to lorlatinib, the most advanced ROS1i known against the ROS1G2032R. Collectively, these results suggest the promising potential of SAF-189s for the treatment of patients with the ROS1 fusion G2032R mutation who relapse on crizotinib. It is now recruiting both crizotinib-relapsed and naive ROS1-positive NSCLC patients in a multicenter phase II trial (ClinicalTrials.gov Identifier: NCT04237805).